2005
DOI: 10.1007/s00404-005-0008-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for conversion to laparotomy during laparoscopic management of an ectopic pregnancy

Abstract: Less experienced surgeon, BMI > 30 kg/m2, and large amount of free fluid on ultrasound increase the risk of conversion to laparotomy during laparoscopic management of ectopic pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 9 publications
4
12
1
Order By: Relevance
“…Based on these measures, our results compare favorably with previous reports of laparoscopy in ectopic pregnancy [2,6,11], adnexal torsion [12][13][14], hemorrhagic ovarian cyst [15], and PID ± TOA [16], even when these procedures were performed by experienced surgeons.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Based on these measures, our results compare favorably with previous reports of laparoscopy in ectopic pregnancy [2,6,11], adnexal torsion [12][13][14], hemorrhagic ovarian cyst [15], and PID ± TOA [16], even when these procedures were performed by experienced surgeons.…”
Section: Discussionsupporting
confidence: 88%
“…Although the associated factors that modify these parameters after elective laparoscopic gynecologic procedures have been studied previously [1,8], little is known about gynecologic emergencies [6]. At the time of the present study, no investigation had specifically addressed these associated factors across the entire spectrum of laparoscopic treatment of gynecologic emergencies.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Far fewer complications occur during laparoscopy when the procedure is performed by an experienced surgeon, in comparison to when the procedure is performed by a novice surgeon. [5][6][7] Tackacs et al found that surgeon inexperience was significantly associated with unintended laparotomy during laparoscopic management of an ectopic pregnancy. 7 Compared to open procedures, laparoscopy is more technically demanding and less efficient due to reduced dexterity, impaired vision, and tactile feedback.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Tackacs et al found that surgeon inexperience was significantly associated with unintended laparotomy during laparoscopic management of an ectopic pregnancy. 7 Compared to open procedures, laparoscopy is more technically demanding and less efficient due to reduced dexterity, impaired vision, and tactile feedback. 8,9 The learning curve to reach the desired level of proficiency in laparoscopic skills is extensive.…”
Section: Introductionmentioning
confidence: 99%